Perfluoroalkyl substances in umbilical cord serum and gestational and postnatal growth in a Chinese birth cohort. (July 2018) - Cao, Wencheng; Liu, Xiao; Liu, Xiaofang; Zhou, Yan; Zhang, Xiaotian; Tian, Haoyuan; Wang, Jin; Feng, Shixian; Wu, Yongning; Bhatti, Parveen; Wen, Sheng; Sun, Xin
Abstract: Although animal studies have found that perfluoroalkyl substances (PFASs) affect gestational and postnatal growth, the epidemiological findings are limited and not in agreement. We explored the associations of PFAS concentrations in umbilical cord blood with gestational and postnatal growth in China. Three hundred thirty-seven singleton newborns and their mothers were recruited from November 2013 to December 2015 in Zhoukou City, China. Umbilical cord blood was collected to measure eleven PFASs by liquid chromatography-mass spectrometry. The index of gestational and postnatal growth contained fetal weight, length, and head circumference. These were obtained at birth and at the follow-up investigation (mean 19 months). Exposed to higher perfluorooctanoic acid (PFOA) were connected with reduced length at birth ( p for trend = 0.01) and decreased postnatal weight (β = −429.2 g; 95% CI: −858.4, −0.121 for 2nd VS. 1st). Exposed to perfluoroundecanoic acid (PFUdA) were positively associated with indications of gestational growth and postnatal growth ( p for trend = 0.02 for birth length; p for trend = 0.04 for postnatal length). Exposed to higher perfluorododecanoic acid (PFDoA) were associated with lower birth weight (β = −122.9 g, 95% CI: −244.7 to −1.2 for 2nd VS. 1st), but higher postnatal length ( p for trend = 0.03). Neonates in the highest exposure group of per-fluorohexanesulfonate (PFHxS) showed decreased birth length (β = −0.33 cm, 95% CI: −0.68 to −0.01, for 2nd VS. 1st), but increased postnatal head circumference ( p for trend = 0.04). Increased PFOA concentrations was associated with shorter birth length only in girls ( p for trend = 0.04), suggesting that the effect of PFASs on gestational growth were different between boys and girls. In utero exposure to PFASs may affect gestational and postnatal growth. Highlights: Prenatal PFASs exposure may be associated with altered gestational and postnatal growth. In utero exposure to PFOA was associated with decreased birth length. PFDoA (12 carbon) levels were negatively associated with birth weight, but positively associated with postnatal length. The PFAS levels in China were generally lower than those determined in developed countries.